Perancangan Sistem Pendukung Keputusan Untuk Menentukan Penerima Dana Bantuan Umkm Menggunakan Metode Simple Additive Weighting (SAW) - Intan Fadilah Heryan (2022)
The pandemic that occurred in 2020 in Indonesia resulted in many people racking their brains to keep their income after being laid off for several reasons. One way is to open your own business or MSME (Micro, Small and Medium Enterprises). MSMEs that are established can be of various types, such as food, home appliances, fashion, skin care, cosmetics and so on. With so many new MSMEs, the government created a program to help business owners by providing business funding assistance through Bank BRI and the Cooperatives, Small and Medium Enterprises, Industry and Trade Office (DKUKMPP). However, in determining which MSMEs should be prioritized, a decision support system is needed that can help DKUKMPP employees know which MSMEs they are helping first. The Decision Support System (DSS) is expected to be able to provide solutions to problems to determine the right decisions, quickly and not misdirected. One method that can be used in DSS is the Simple Additive Weighting (SAW) method. DSS with SAW is carried out in several stages and consider several supporting criteria in collecting and getting a subjective decision result. The criteria needed in this study are the completeness of the MSME documents, the required capital, the income generated and the workforce employed. To create the system, the stages of problem formulation, data collection, requirements analysis, system design, implementation of the designed system and system testing are carried out. The final result of this research has been the establishment of an DSS which determines which MSMEs are prioritized to receive aid funds through several features that apply the SAW method. Keywords: MSMEs, Decision Support Systems (DSS), SAW.